Direct Binding between Pre-S1 and TRP-like Domains in TRPP Channels Mediates Gating and Functional Regulation by PIP2 - Wang Zheng; Ruiqi Cai; Laura Hofmann; Vasyl Nesin; Qiaolin Hu; Wentong Long; Mohammad Fatehi; Xiong Liu; Shaimaa Hussein; Tim Kong; Jingru Li; Peter E. Light; et al. (Cell Reports, 2018)
Summary: Transient receptor potential (TRP) channels are regulated by diverse stimuli comprising thermal, chemical, and mechanical modalities. They are also commonly regulated by phosphatidylinositol-4,5-bisphosphate (PIP2), with underlying mechanisms largely unknown. We here revealed an intramolecular interaction of the TRPP3 N and C termini (N-C) that is functionally essential. The interaction was mediated by aromatic Trp81 in pre-S1 domain and cationic Lys568 in TRP-like domain. Structure-function analyses revealed similar N-C interaction in TRPP2 as well as TRPM8/-V1/-C4 via highly conserved tryptophan and lysine/arginine residues. PIP2 bound to cationic residues in TRPP3, including K568, thereby disrupting the N-C interaction and negatively regulating TRPP3. PIP2 had similar negative effects on TRPP2. Interestingly, we found that PIP2 facilitates the N-C interaction in TRPM8/-V1, resulting in channel potentiation. The intramolecular N-C interaction might represent a shared mechanism underlying the gating and PIP2 regulation of TRP channels.